Evaluasi Sistem Akuntansi Penghapusan Barang Milik Daerah Melalui Mekanisme Pemindahtanganan Hibah di Badan Pengelola Keuangan dan Aset Daerah Kabupaten Tabalong - Paskahyati Simanjuntak, Berlianita; Farida, Lea Emilia; Hikmahwati (P3M Politeknik Negeri Banjarmasin, 2024)
Regional Assets (Barang Milik Daerah/BMD) is one of the critical elements in government administration, and their management must comply with the prevailing laws and regulations, including in the process of disposal. The disposal of regional assets is conducted to reduce maintenance and operational burdens, thereby making government expenditures more efficient. This study aims to evaluate the accounting system for BMD disposal through the grant transfer mechanism at the Regional Financial and Asset Management Agency (BPKAD) of Tabalong Regency. The research employs a case study method with qualitative data obtained through interviews and document collection. The findings reveal that the implementation of the accounting system for BMD disposal through the grant transfer mechanism at BPKAD Tabalong Regency has been effective. This is due to the alignment of related functions, the use of appropriate documents, the maintenance of accurate records, and the procedural network that constitutes the system, all of which comply with Tabalong Regent Regulation Number 22 of 2020 concerning the System and Procedures for Managing Regional Assets.